Tinjauan Lokasi Holding Point Pesawat Visual Flight Rules (VFR) Manado Control Zone - Rijaluddien Muh Ibrahim; Surya Tri Saputra (Politeknik Penerbangan Indonesia Curug, 2024)
Air traffic services at Sam Ratulangi International Airport Manado have a number of VFR flight traffic. In providing air traffic services, the air traffic controller of Perum LPPNPI Manado Branch is guided by predetermined procedures. VFR aircraft that arrive do not have a holding point. VFR aircraft are given orbit instructions to maintain separation from IFR aircraft arriving or holding at MNO VOR/DME. However, ATC does not know exactly how the orbit maneuvers of aircraft and VFR aircraft that will approach runway 36 from the VFR Manado-Lilang route can hinder aircraft that will depart with visual runway 18 via Airmadidi. The solution is to create a Holding Point for VFR aircraft to improve approach control optimization service at Perum LPPNPI Manado Branch. In this study the authors used a qualitative descriptive data analysis research technique. The data studied contains words or sentences obtained from interviews or observations.